2016
DOI: 10.1002/pssa.201600588
|View full text |Cite
|
Sign up to set email alerts
|

Local vibrational modes of interstitial boron–interstitial oxygen complex in silicon

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.In the present work, we report local vibrational mode (LVM) related absorption lines which are assigned to the complex incorporating interstitial boron and interstitial oxygen atoms (B i O i ), a possible precursor of the center responsible for lightinduced degradation (LID) in solar cells produced from boron-dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
5
1
Order By: Relevance
“…In the previous studies , it was shown by DLTS that the B i C s complexes in boron‐doped Cz‐Si arise synchronously with the dissociation of B i O i defects. The annealing temperature for B i O i , according to the studies is 150–200 °C, i.e., slightly higher than that for B i B s defects observed by us. Taking into account the closeness of these two annealing processes, it can be concluded that B i atoms liberated as a result of the dissociation of both B i B s and B i O i are involved in the formation of B i C s defects in the oxygen‐rich material.…”
Section: Resultscontrasting
confidence: 51%
See 1 more Smart Citation
“…In the previous studies , it was shown by DLTS that the B i C s complexes in boron‐doped Cz‐Si arise synchronously with the dissociation of B i O i defects. The annealing temperature for B i O i , according to the studies is 150–200 °C, i.e., slightly higher than that for B i B s defects observed by us. Taking into account the closeness of these two annealing processes, it can be concluded that B i atoms liberated as a result of the dissociation of both B i B s and B i O i are involved in the formation of B i C s defects in the oxygen‐rich material.…”
Section: Resultscontrasting
confidence: 51%
“…Therefore, the interpretation of the observed bands requires additional studies. The set of LVMs at 991, 721, and 550 cm ­−1 in work is associated with B i O i ‐related defects. In a recent study , the absorption bands at 739.4, 759.6, and 780.9 cm ­−1 were identified as LVMs associated with B i B i defects, and the line at 923.5 cm ­−1 was ascribed to the complexes involving interstitial boron and interstitial oxygen atoms.…”
Section: Introductionmentioning
confidence: 99%
“…[7,21] A new set of absorption bands positioned at about 538, 550, 688, 721, 756, and 991 cm À1 was identified as LVMs of the B i O i complex. [22] The studies performed by deep-level transient spectroscopy and electron paramagnetic resonance methods indicate that, at the injection of minority carriers, a significant increase in the rate of annealing of B i can be observed in accordance with the Bourgoin-Corbett mechanism. [4,23] Recently, it was shown that the enhanced diffusion of interstitial boron can occur also during the irradiation of samples at a temperature of 80 K. [24,25] The absorption spectra of the as-irradiated samples contain no LVMs associated with interstitial boron, but the LVMs of defects, whose composition includes interstitial boron, were registered.…”
Section: Introductionmentioning
confidence: 88%
“…Two LVMs at 733 and 760 cm –1 were assigned to the B i B s complex . A new set of absorption bands positioned at about 538, 550, 688, 721, 756, and 991 cm −1 was identified as LVMs of the B i O i complex …”
Section: Introductionmentioning
confidence: 99%
“…Rather than ignoring or filtering away PFID as a "coherent artifact" of pump-probe measurements [28], PFID may serve as a powerful tool in optics and ultrafast spectroscopy by providing subtle features that, when modeled accurately, yield accurate dephasing rates. These advances will be of interest in (i) chemical physics, where PFID as a spectroscopic technique is widely applicable to study the ultrafast vibrational dynamics of solidstate, liquid-phase, and gas-phase molecular systems [20][21][22][23][24][25][26][27]; (ii) molecular chemistry, where using PFID to accurately measure T 2 across different vibrational modes would advance the molecular design of popular systems such as modified graphene [40] and dye molecules [41], and could also uncover key molecule-environment interactions [42]; and (iii) semiconductor and quantum physics, where PFID may be used to probe defect-lattice interactions within tailored defect environments in diamond, as in the present work, or indeed in other semiconductor materials with important functional defects, such as GaN [43], silicon [44], or metal oxides [45]. The FTIR spectrum of S1 could not be resolved for N 0 s and A=B centers.…”
mentioning
confidence: 89%